An analysis of the distribution of bone and soft tissue sarcoma diagnoses and their disparities in Southwest Germany: a multicenter approach - Calukovic, Branko; Benzler, Katrin; Carter, Mary E.; Daigeler, Adrien; Thiel, Johannes T.; Jakob, Jens; Kasper, Bernd; Egerer, Gerlinde; Apostolidis, Leonidas; Braig, David; Hettmer, Simone; Blattmann, Claudia; et al. (Frontiers in Oncology, 2025)
IntroductionSarcoma is a rare and highly heterogeneous family of mesenchymal tumors. The experience and interdisciplinary approach of specialized high-volume sarcoma centers has a significant impact on disease treatment and outcome for patients. The aim of this retrospective, real-world, multicenter study was to evaluate geographic distribution of sarcoma cases in Southwest Germany and visually depict possible underrepresented areas of sarcoma primary diagnoses. Such descriptive information may indirectly guide future referral patterns and outreach activities of specialized sarcoma centers.MethodsThe absolute number and incidence of sarcoma patients obtained from the Baden-Württemberg Cancer Registry were compared with the data from five individual, high-volume, specialized sarcoma centers. Furthermore, we used a “White-Spot Analysis” as a novel cost-effective approach in epidemiological and public health research for analyzing health care coverage in sarcoma care.ResultsA total of 4,087 sarcoma patients living in the German Federal State of Baden-Württemberg between 2019 and 2022 were included in this study. Of these, 1,650 patients (40%) were treated primarily in specialized sarcoma centers whilst 2,437 patients (60%) received treatment for sarcoma outside of the five main high-volume centers, in underrepresented areas identified through White-Spot Analysis. The sarcoma incidence in Baden-Württemberg was calculated with our data to be 9.18/100,000 inhabitants per year.DiscussionIn future, the access to high-volume centers needs to be facilitated in order to minimize the observed discrepancies between treatment in specialized sarcoma centers and low-volume centers in Southwest Germany. Our analysis highlights such discrepancies and may support future efforts to improve outcomes for sarcoma patients.